PERFORMANCE CAPTURING PENCHAK SILAT MOVEMENT AS A REFERENCE STUDY FOR CONTENT CREATORS - Hario Sasongko (Bina Nusantara University, 2019)
Content creators like flmmakers, comic artists, designers or animators, are always wanted to be inspired. Some researched have found that a theme that will never be dried out to explore is the theme about culture. The beauty but deadly characteristic of Penchak Silat could be one of Indonesian unique cultural wealth with great potential as a source for any creative content. But animating or mimicking the movement of Penchak Silat is not an easy task for animators or any content creators, it requires deeper on both pieces of knowledge of motion and self-defense itself, which sometimes can only be understood by someone who spent their life trained in this martial art. This paper method is a documented experiment of using motion capture as a quantitative tool which complements the often qualitative approaches of user observations to study captured movements of Penchak Silat in the form of digital data. In this research a real Penchak Silat practitioner were set of tasks to performed jurus or Penchak Silat codifed movements. The motions of the research subjects were captured by a set of simple motion capture device with four PlayStation cameras. The data recorded through the motion capture system were translated into a rigged 3D model. Conclusions were drawn on the potential use of motion capture tool that can gain beneft to any content creator, based on the accuracy of the body mechanics and complexity of Penchak Silat movements that’s been recorded. Another goal is to provide a ready to use reference for animators, enabling them to bring easier and more eﬀective workﬂows in animation production.